“Genome design” model: Evidence from conserved intronic sequence in human–mouse comparison - Vinogradov, Alexander E. (Genome Research, 2006)
Introns are shorter in housekeeping genes than in tissue- or development-specific genes. Differing explanations have been offered for this phenomenon: selection for economy (in housekeeping genes), mutation bias or “genomic design.” The large-scale implementation in this present paper of a rigorous local sequence alignment algorithm revealed an unprecedented fraction of evolutionarily conserved DNA in human–mouse introns (∼60% of human and ∼70% of mouse intron length remained after masking for lineage-specific repeats). The length distributions of both conserved and nonconserved regions are very broad but show peaks close to nucleosomal and dinucleosomal DNA. Both the fraction of conserved sequence and its absolute length were higher in introns of tissue-specific genes than housekeeping genes. This difference remained after control for between-species identity of the conserved fraction, mutation rate, and GC content. In a more direct control, the product of the conserved sequence fraction and the between-species identity of this fraction (which can be considered to be the fraction of conserved nucleotides) was greater in introns of tissue-specific genes than housekeeping genes. Neither the fraction of intron length covered by repeats nor the balance of small insertions and deletions (indels) can explain the greater length of introns in tissue-specific genes. The length of the conserved intronic DNA in a gene is correlated with the number of functional domains in the protein encoded by that gene. These results suggest that the greater length of introns in tissue-specific genes is not due to selection for economy or mutation bias but instead is related to functional complexity (probably mediated by chromatin condensation), and that the evolution of the bulk of noncoding DNA is not completely neutral.
10.1101/gr.4318206